Integration and Polymorphism of Knowledge in Higher Education. Part II - Klepko, Sergiy (Filosofiya osvity. Philosophy of Education, 2006)
Multidisciplinary and transdisciplinary problems, search of a new paradigm of post-disciplinary university are examined in the second part of the article. Analysis of multidisciplinary integration shows its fundamental restrictions. Opposing idea of rational alternatives to the old ideal of science unity, the author emphasis the heterogeneity of integration in the modern science and considers different types of possible knowledge integration.